2005
DOI: 10.1254/jphs.fpj04043x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Herbal Medicine Toki-shakuyaku-san on Blood Pressure in an Nω-Nitro-L-Arginine Methyl Ester-Induced Pre-eclampsia Rat Model During Pregnancy and the Postpartum Period

Abstract: Abstract. The chronic inhibition of nitric oxide (NO) synthesis with N ω -nitro-L-arginine methyl ester (L-NAME) in pregnant rats induces a pre-eclampsia-like syndrome, including hypertension. We have previously reported the beneficial effects of Toki-shakuyaku-san (TS) in this model. In the present study we demonstrated the anti-hypertensive effect of TS in preeclampsia produced by prolonged L-NAME-infusion during the postpartum period. Analysis of blood sex steroids suggested that the level of progesterone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is because, apart from causing vasoconstriction, preeclampsia has a complex pathophysiology. Unlike many other antihypertensive drugs, TS does not lower blood pressure in normotensive pregnant rats [29]. This suggests that TS might be used more safely during pregnancy.…”
Section: Plos Onementioning
confidence: 88%
See 2 more Smart Citations
“…This is because, apart from causing vasoconstriction, preeclampsia has a complex pathophysiology. Unlike many other antihypertensive drugs, TS does not lower blood pressure in normotensive pregnant rats [29]. This suggests that TS might be used more safely during pregnancy.…”
Section: Plos Onementioning
confidence: 88%
“…Some researchers have demonstrated the ameliorative effects of TS on preeclampsia, fetal growth restriction, and recurrent pregnancy loss [29,30]. It has been reported that TS regulates the immunity of invariant natural killer T cells during early pregnancy (in mice), and thus reduces the rate of pregnancy loss [31].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…TSS could also affect the circulatory functions. It has been reported that TSS improves hypertension, in progesterone dependent preeclampsia rats (Takei et al, 2005). Moreover, TSS at a single dose improves blood flow in oketsu and normal mice (Ueda et al, 2004).…”
Section: Effects Of Tss On Ach Levels In the Dhmentioning
confidence: 94%